Ketika Upward Comparison Tidak Menjatuhkan: Eksperimen Paparan Konten Instagram terhadap State Self-Esteem - Muhammad Qushayyi Shidqi; Daneila Ramadhani Ichsan; Syifa Nurmayanti; Noor Sabah; Reza Valevi; Nazwa Ashila Salwa; Nalarita Brillianty; Valendra Granitha Shandika Puri (INSAN Jurnal Psikologi dan Kesehatan Mental, 2026)
The intensive use of Instagram among adolescents and young adults makes this platform a significant context in the formation of self-evaluation, particularly state self-esteem. Based on social comparison theory, this study aims to examine the effect of exposure to Instagram content with different social comparison directions on changes in state self-esteem. This replication study employed a mixed-factorial experimental design; 35 college students were randomly assigned to three groups and assessed for their state self-esteem scores before and after the intervention. The results showed that only the upward comparison group experienced a significant increase in state self-esteem. These findings challenge previous assumptions regarding the negative impact of upward comparison, as participants appeared to interpret others’ achievements as a source of motivation. This study contributes to a broader understanding of the dynamics of self-esteem in a digital context and the importance of psycho-literacy in responding to social media content.